A Direct, Modular, and Efficient Construction of the PCP Structural Motif through Coupling of Manganese Carbyne Complexes with Phosphines. Issue 8 (30th January 2014) - Valyaev, Dmitry A.; Bastin, Stéphanie; Utegenov, Kamil I.; Lugan, Noël; Lavigne, Guy; Ustynyuk, Nikolai A.
Abstract Easily available carbyne complexes of manganese were used as a source of carbyne fragments in an unconventional synthesis of backbone‐substituted diphosphinomethanes and cyclic P‐ylides upon coupling with secondary or tertiary phosphines, respectively, followed by demetalation under mild conditions.